Impact of Service Quality, Customer Dissatisfaction and Variety-Seeking on Brand Switching Intention - Tri Endang Yani; Yuli Budiati; Ahmad Ershaid Nusair; Aprih Santoso (Relevance: Journal of Management and Business, 2022)
Many students wish to continue their studies but choose a different college or intend to do brand switching. On the other hand, universities want students to continue their studies back at their home institutions. This study aims to analyze the effect of perceptions of service quality, customer dissatisfaction and variety-seeking on Brand Switching Intention in Higher Education. The population in this study were students who were still active in higher education. Samples were taken as many as 50 people with the purposive sampling method. The criteria for respondents were students who had an interest in further study. The analysis method used is multiple linear regression. The results showed that the perception of service quality did not affect brand switching intention. Meanwhile, customer dissatisfaction and Variety seeking have a positive and significant effect on brand switching intention. The coefficient of determination is 0,544, of the variation in brand switching intention, which the three independent variables can explain. At the same time, the rest is influenced by other variables outside the research. Â  Keywords: service quality, customer dissatisfaction, Variety seeking, Brand switching intention